FOREIGN DIRECT INVESTMENT, ECONOMIC GROWTH AND EMPLOYMENT:VAR METHOD FOR UZBEKISTAN - Rakhmatillo, Ergashev; Anvar, Kobilov; Sukhrob, Makhmudov (The journal of contemporary issues in business and government, 2021)
This paper examines the annual data series from 2000 to 2020 and analyses the interaction among foreign direct investment, economic growth and employment through VAR model.Augmented Dickey-Fuller test, Grangercausality test and variance decompositionresults show that the foreign directinvestment has a positive effect on economic growth and employment, and the economic growth has a positiveeffect on foreign direct investment and employment. There is a bi-directional causality between employment and economic growth.Meanwhile, theforeign direct investment can also result in an increase in the employment.Simultaneously, the high speed economicgrowth can improve the employment in Uzbekistan.More importantly, this paper providesrecommendationsfor Uzbekistan’s government to settle social problems such as employment and economic growth.Specifically, at present, Uzbekistan’s government should encourage foreign investors to invest in Uzbekistan because itcan be beneficial to employment and economic growth in Uzbekistan. Of course, the structure of employment alsoshould be optimized so as to keep high speed economic growth.